KAJIAN KAPASITAS DAN EFEKTIVITAS RESIN PENUKAR ANION UNTUK MENGIKAT KLOR DAN APLIKASINYA PADA AIR - Antara, I K. G.; Budiarsa Suyasa, I W.; Bawa Putra, A. A. (Jurnal Kimia (Journal of Chemistry), 2012)
This paper reports a research on the capacity and efficiency of resin anion exchange on chloride in a batch system. The system was then applied to chloride level in spring water in Sedang Village. Chloride content analysed were using argentometry methode . The results of the research showed that resin was potential to reduce chloride level below Water Quality Limit for (Group B). Its capacity was 0.6462 mg/g and saturating time was 260 minutes. Its effectiveness between 64.50% - 97.04%. The analysis of spring water in Sedang Village showed that these springs were contaminated with 260.33 – 295.83 ppm chloride. The resin exchange applied to these waters reduced the chloride levels to the level below the Guideline Limit for the 250 mg/L purposes (Group B).
Keywords: capacity, efficiency, resin, chloride